Cooking routine practices among Malaysian working women / Siti Khuzaimah Abu Bakar ...[et al.] - Abu Bakar, Siti Khuzaimah; Mohd Salehuddin, M. Z.; Kamaruddin, Mohd Syaquif Yasin; Saiful Bakhtiar, Mohd Faeez (Universiti Teknologi MARA Cawangan Selangor, 2012)
Working is becoming a necessity and one of the most vital elements in this modern era for bachelors and family couples for economic needs. Because of their work, women need to sacrifice many things together with a crucial household responsibility which is cooking. Owing to the increasing number of working women, this study therefore empirically investigated the issues related to cooking routines among working women, particularly in Malaysia. Self - administered questionnaires were distributed among the working women. Through the descriptive analysis, some meaningful insights into the issues of interest were obtained and the findings overtly revealed that working time, the economy and dietary patterns are factors that leave women with no other options but to opt for convenience cooking practices for their family dinner during weekdays. Despite this, to maintain a pleasant family relationship and to love and nurture family members, particularly the growing ones, home cooking is performed during weekends.